Effect of Bonds Maturity Date, Interest Rates, Inflation, Exchange Rates and Foreign Exchange Reserves on Yield To Maturity of Government Bonds 2014-2020 - Ditha Varirahartia; Bambang Santoso Marsoem (Jurnal Syntax Admiration, 2022)
This study aims to analyze the effect of maturity date, interest rate, exchange rate, inflation and foreign exchange reserves on the yield to maturity of Indonesian government bonds for the period 2014-2020. The analysis is using panel data analysis. The results showed that the maturity level of bonds (X1), interest rates (X2), had a positive and statistically significant effect on yield to maturity. The inflation (X3) and has a negative and significant effect, while the exchange rate (X4) has no significant effect but has a positive relationship.  Foreign exchange reserves (X5) have a negative and significant effect. The exchange rate does not have a significant effect. This is not in accordance with the previous theory, because the sample limitation in this study only uses bonds with Rupiah currency